The Implementation of Blended Learning Strategy to Face 21st Century: Library Research - Wirahyuni, Kadek; Suwiwa, Gede (International Proceedings of Nusantara Raya, 2023)
The present study aimed at investigating the characteristics of blended learning strategy, its benefits, its challenges, and teachers’ role. The study was designed in library study in which all the data were obtained from reviewing related articles. Some steps were conducted, namely identifying topic, formulating research questions, planning research, making use as source of data, setting the criteria, limiting the aspects, and interpreting the obtained data. The results of the study show that 1) the characteristics of blended learning depend on combination of online and offline setting and technology; 2) the benefits cover the flexibility of blended learning strategy, different design of learning to be done, easy access to obtain learning resources, concerning student-centered-learning, and training students’ critical thinking; 3) the challenges cover four main problems, namely technical problems, lack of self-regulation, limited social interaction, and technological skills; and 4) teachers have role as motivator, manager, and facilitator. Blended learning strategy can be a useful learning strategy in the 21st century learning. It is suggested to conduct further study on the effectiveness of blended learning strategy considering the level of education.